Treating maternal depression: understanding barriers and facilitators to repetitive transcranial magnetic stimulation treatment in Canada-a protocol - Al-Shamali, Huda F.; Jackson, Margot; Zinchuk, Nataliia; Modanloo, Setayesh; Wong, Gina; Cao, Bo; Burback, Lisa; Li, Xin-Min; Greenshaw, Andrew; Zhang, Yanbo (Frontiers in Psychiatry, 2023)
Background: Peripartum depression (PPD) is a serious public health issue associated with severe and potentially long-term adverse maternal and child developmental outcomes. Suicide and overdose, for example, accounts for up to a third of maternal deaths. A current depression diagnosis with no active treatment is a common risk factor for maternal suicide. Repetitive transcranial magnetic stimulation (rTMS) is a non-pharmacological treatment that has recently shown some promise as an effective treatment with limited side effects for PPD, but more research is required. This study aims to identify current barriers and potential facilitators for women with PPD accessing treatment in general, and rTMS specifically. Methods: This study will consist of two anonymous, self-administered surveys, focus groups, and interviews. A descriptive interpretative approach will be employed, and thematic analysis will be completed for the focus groups and interviews. Participants who are currently, or have previously experienced depressive symptoms, as well as health providers will be recruited. Our study will follow an equity, diversity, and inclusion (EDI) perspective on sex, gender, and ethnicity and the Gender-based Analysis Plus (GBA+) analytic tool will be used. Both a qualitative and quantitative analysis of the data will be conducted. Discussion: We expect to find education and accessibility to be primary treatment barriers for persons with PPD. Identifying and addressing barriers is a critical first step towards the devolvement of initiatives that can work towards improving mental health in this population.